2015
DOI: 10.1002/maco.201508380
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ce on inclusions and corrosion resistance of low‐nickel austenite stainless steel

Abstract: Effects of Ce on the corrosion resistance of low‐nickel austenite stainless steel containing Ce from 0.005 to 0.022 wt% were investigated in 3.5 wt% NaCl solution, 5 wt% H2SO4 solution, 1 mol/L NaHCO3 and 0.5 mol/L Na2CO3 solution. The results demonstrate that addition of Ce to low‐nickel austenite stainless steel forms multi‐phase inclusions containing CeAlO3 and Ce2O2S that can prevent corrosion. Ce addition to steels increases the corrosion resistance owing to metamorphic inclusions and the improvement of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Other studies have shown that the solid solution of rare earth cerium in steel can enhance the corrosion resistance of the steel matrix [17]. Rare earth ce- rium can increase the polarization resistance and free corrosion potential, changing the structure of the compact layer by forming a covering layer which has good adhesiveness and excellent corrosion resistance.…”
Section: Influence Of Rare Earth Cerium On the Corrosion Resistance Omentioning
confidence: 99%
“…Other studies have shown that the solid solution of rare earth cerium in steel can enhance the corrosion resistance of the steel matrix [17]. Rare earth ce- rium can increase the polarization resistance and free corrosion potential, changing the structure of the compact layer by forming a covering layer which has good adhesiveness and excellent corrosion resistance.…”
Section: Influence Of Rare Earth Cerium On the Corrosion Resistance Omentioning
confidence: 99%
“…RE elements can significantly reduce the interfacial tension of material and driving force of grain growth, hinder the corresponding atoms from liquid phase to solid phase due to a low equilibrium partition coefficient, [12][13][14][15] inducing the deterioration of heterogeneous nuclei and inhibiting the grain growth during annealing. of 2.5 μm observed in Y-doped sample A2 can effectively affect the texture evolution.…”
Section: Inclusion Microstructure and Texture Of Annealed Sheetsmentioning
confidence: 99%
“…As is well known, based on vacancy diffusion mechanism, rare earth Ce acted as a resistance for the interfacial tension of liquid-solid two-phase interface can hinder the corresponding atoms from the liquid phase to solid phase, which significantly decrease the nucleation energy and increase nucleation rate of austenite grains. 18) The relation between average grain size and grain growth velocity can be expressed in the following equation: 19) d I Q where d is the average size of austenite grains of annealed samples, as well as ν and I represent grain growth velocity and nucleation rate, respectively. In this study, both the annealed temperature and cooling speed are invariable, as such, the velocity of grain growth is a constant.…”
Section: Grain Boundarymentioning
confidence: 99%